Peer Education: Health Education for Adolescent Girls to Prevent Adolescent Sexual Risk Behaviors - Sri Yona; Elly Nurachmah; Anggri Noorana Zahra; Cut Sarida Pompey (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Adolescent girls aged 15-24 are at risk of contracting sexually transmitted diseases such as HIV/AIDS. The existence of adolescent promiscuity, inadequate knowledge of adolescents about HIV/AIDS, and lack of communication with parents on adolescent reproductive health are some related factors to the increased number of adolescents infected with sexually transmitted diseases and HIV/AIDS. Based on these situations, providing health education to adolescents is an alternative solution. The activities were carried out by implementing health education for teenage girls, conducted in four sessions. All sessions were held online, with interactive discussion methods, role play and demonstrations. A total of 18 adolescent girls participated in this activity. The final results showed that there is an increasing mean score of post-test on HIV knowledge (0.5), adolescent reproductive health (0.44), and self-esteem (0.39). There are no significant different between pre and post-test for the level of knowledge on HIV, adolescent reproductive health, adolescent risk behavior and self-esteem. Only risky behavior does not demonstrate an increase in the mean score. Providing health education to teenage girls has improved their knowledge and understanding of HIV/AIDS and adolescent reproductive health and increased adolescent self-esteem. However, these activities did not affect the score of teens’ behavior change. It was due to the duration of health education was not sufficient to change their behavior.